PEMBERDAYAAN MAHASISWA MELALUI PRAKTEK MINUMAN ANEKA BUAH DALAM MENINGKATKAN MINAT WIRAUSAHA MAHASISWA AGRIBISNIS - Leni Saleh; Milawati Saranani; Ulyasniati; Milyan (Bersama : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of the activity is to hold this community service activity, to foster creativity and an entrepreneurial spirit among the younger generation, especially students, so that they can use their time for creative and productive activities through the business of fresh fruit juices. The selected student participants totaled 30 people, the stages of the activity were lectures delivering material and practice. The community service activities carried out for students of the Agribusiness Study Program went well, the participants were enthusiastic in participating in the training activities. Through this training activity, students become motivated and can make agricultural processed products, especially fruits, into fruit juice drinks whose ingredients are easily available and the manufacturing process is very easy. The results of the evaluation were 80% or 24 student participants in making fruit juice drinks were successful and did not experience difficulties and 20% or 6 student participants who were still not successful in making fruit juices, this was because the fruit had been cooked for too long and the dosage for making the drinks was not appropriate instructions from the supervisor. Keywords: Empowerment, Students, Beverages, Fruits, entrepreneurship